Sri Lanka : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper discusses measures needed for structural transformation in Sri Lanka. The government has ambitious plans to achieve upper middle-income country status in 2025 by transforming Sri Lanka in an Indian Ocean Hub for trade, investment, and services. Stable and transparent regulatory systems would make Sri Lanka's business environment more attractive for long-term investment and support trade integration. Reviewing trade barriers and developing a phased and sequenced strategy for gradual removal of restrictions is a first necessary step toward enabling more competitive trade. In this regard, the authorities' decision to gradually rationalize para-tariffs and set up automated approval systems is a welcome step. Ongoing open consultative processes on reform strategies can also help building public consensus in support of these important objectives.